Protein kinase CK2 modulates HSJ1 function through phosphorylation of the UIM2 domain - Ottaviani, Daniele (Hum Mol Genet, 2017)
HSJ1 (DNAJB2), a member of the DNAJ family of molecular chaperones, is a key player in neuronal proteostasis maintenance. It binds ubiquitylated proteins through its Ubiquitin Interacting Motifs (UIMs) and facilitates their delivery to the proteasome for degradation. Mutations in the DNAJB2 gene lead to inherited neuropathies such as Charcot-Marie-Tooth type-2, distal hereditary motor neuropathies, spinal muscular atrophy with parkinsonism and the later stages can resemble amyotrophic lateral sclerosis. HSJ1 overexpression can reduce aggregation of neurodegeneration-associated proteins in vitro and in vivo; however, the regulation of HSJ1 function is little understood. Here we show that CK2, a ubiquitous and constitutively active protein kinase, phosphorylates HSJ1 within its second UIM, at the dominant site Ser250 and the hierarchical site Ser247. A phospho-HSJ1 specific antibody confirmed phosphorylation of endogenous HSJ1a and HSJ1b. A tandem approach of phospho-site mutation and treatment with CK2 specific inhibitors demonstrated that phosphorylation at these sites is accompanied by a reduced ability of HSJ1 to bind ubiquitylated clients and to exert its chaperone activity. Our results disclose a novel interplay between ubiquitin- and phosphorylation-dependent signalling, and represent the first report of a regulatory mechanism for UIM-dependent function. They also suggest that CK2 inhibitors could release the full neuroprotective potential of HSJ1, and deserve future interest as therapeutic strategies for neurodegenerative disease.